James Baldwin : the FBI file - Maxwell, William J. (College teacher) (Arcade Publishing, 2017)
"Available in book form for the first time, the FBI's secret dossier on the legendary and controversial writer. Decades before Black Lives Matter returned James Baldwin to prominence, J. Edgar Hoover's FBI considered the Harlem-born author the most powerful broker between black art and black power. Baldwin's 1,884-page FBI file, covering the period from 1958 to 1974, was the largest compiled on any African American artist of the Civil Rights era. This collection of once-secret documents, never before published in book form, captures the FBI's anxious tracking of Baldwin's writings, phone conversations, and sexual habits-and Baldwin's defiant efforts to spy back at Hoover and his G-men. James Baldwin: The FBI File reproduces over one hundred original FBI records, selected by the noted literary historian whose award-winning book, F.B. Eyes: How J. Edgar Hoover's Ghostreaders Framed African American Literature, brought renewed attention to bureau surveillance. William J. Maxwell also provides a substantial introduction and running commentaries that orient the reader and offer historical context, making this book a revealing look at a crucial slice of the American past"--